PASAR PADA MASA KESULTANAN ISLAM BANTEN - Siti Fauziyah (Fakultas Adab dan Ilmu Budaya UIN Sunan Kalijaga Yogyakarta, 2012)
Market has an important role for the labors of trading economic market.In the structure of sultanate economic, Bandar city and Palace city are as thehighest central market networking for the intermediate market center out of theother area from Bandar city and palace and also as local market at the village.Thus, the market is divided in hierarchical networks of centers of economicactivity into the countryside in accordance with the mutual economic relationsbetween the two sides, the city Bandar or the palace and the rural areas. Marketin Banten is the center of trade, both international and local itinerant trade. Inaddition the market in Banten is also an exchange center and a meeting ofprominent merchants and ship captains. Market in Banten is income for Sultanand the government. Sultan not only gets tax from the trading in market but alsoas the resource to get benefit from the trading. Market can be a symbolic ruler.With the market, it can be said that safety is assured in the region to conduct thetransaction. Thus the authorities failed to provide protection to be consideredsubjects for the peaceful conduct of economic activity